Pembelajaran Daring Latsar CPNS From Home dalam Masa Pandemi Covid-19 - Agus Suharsono (SAP (Susunan Artikel Pendidikan), 2020)
This study analyzes the learning of the Whole of Government through online classes at Latsar CPNS from Home during the COVID-19 pandemic at the Yogyakarta Financial Training Center. The method used is quasi experiment. The results of the study are as follows: the average post-test score of the class is 92 or very satisfactory, the highest score per participant with a score of 100 or very satisfying and the lowest is 81 or satisfying. The learning action plan is able to convey material up to 81% -95%. The disadvantages of online learning are the lack of understanding of the material and the constraint of unstable internet connections, while the strengths are interesting, fun, sharpening your dexterity in searching and finding answers. Suggestions for improvement are to add to the discussion of learning material, the form of questions with right-wrong answer choices be replaced by multiple choices, and reduce the number of post-test questions. In general online learning is considered positive and effective by participants so that it can be continued both during the pandemic and the new normal.